1953
DOI: 10.1161/01.cir.7.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Supraventricular Tachycardia Complicating Surgical Procedures

Abstract: Persistent postoperative supraventricular tachycardia, despite adequate therapy, is a bad prognostic sign, and cardiac failure due to, or associated with, arrhythmia responds poorly to treatment. Of the 12 patients (24 per cent) resistent to therapy, eight developed congestive heart failure, with five dying as a result. The preoperative, intraoperative and postoperative factors contributing to the causes of this complication are reviewed, and the therapy, course and end results are discussed.T HE OCCURRENCE of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1954
1954
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 9 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…36,37 In non-cardiac, non-thoracic surgery, POAF occurs relatively infrequently (0.37% for ophthalmic surgery up to 13% for large colorectal surgery). 2530 After thoracic surgery POAF is more frequent, with reported incidences of 9–29%.…”
Section: Epidemiologymentioning
confidence: 99%
“…36,37 In non-cardiac, non-thoracic surgery, POAF occurs relatively infrequently (0.37% for ophthalmic surgery up to 13% for large colorectal surgery). 2530 After thoracic surgery POAF is more frequent, with reported incidences of 9–29%.…”
Section: Epidemiologymentioning
confidence: 99%
“…1,3 Roger et al reported that overall incidence of supraventricular tachycardia was estimated to be less than 1% and in those with an SVT, the incidence of AF and atrial flutter was 30% and 12%, respectively with only 20% of arrhythmias occuring intraoperatively. 4 The aim of this particular case report is to review the management strategies of atrial fibrillation with particular attention given on the management of perioperative atrial fibrillation and prevent further complications. Atrial fibrillation is a common arrhythmia occurring in 0.4-5% of adult population and most of these are not associated with any cardiac disease.…”
Section: Discussionmentioning
confidence: 99%